Discovery of potential biomarkers in oral squamous cell carcinoma using next generation sequencing and proteomic technologies / Jesinda Pauline Kerishnan - Jesinda Pauline, Kerishnan (2018)
Oral cancer patients have one of the lowest survival rates in the world due to its poor prognosis. Early detection and diagnosis using more reliable biomarkers will improve the current survival rate of OSCC patients. The present study aims to identify potential molecular biomarkers associated to OSCC using a combination of genomics and proteomics technologies. First, the demographic characteristics of patients were analysed to identify and determine the suitable cohort for this study. Demographic study of 208 OSCC patients and 134 non-OSCC controls confirmed that the local female Indian community that practices betel quid chewing is at the highest risk of developing OSCC and past exposure to HPV16 infection could contribute to the onset of OSCC. To identify potential OSCC biomarkers, 12 pairs of gDNA from OSCC and its adjacent non-malignant tissues were subjected to exome sequencing. The sequencing analysis identified 50 somatically mutated genes in OSCC of which CASP8, USP40, NOTCH1, and COL11A1 were further evaluated as candidate biomarkers. These 4 genes were previously reported in various cancers including the head and neck cancer. However, the exact association of USP40 and COL11A1 mutations in OSCC were not fully described. Most of the SNVs identified in these genes were found to be novel in OSCC and were characterized as deleterious. Finally, genotyping of the candidate genes using Fluidigm SNP Genotyping in a larger population of 167 OSCC patients successfully identified USP40 as a promising biomarker for OSCC. In the proteomic study, sera of 25 OSCC patients and 25 healthy controls were subjected to 2-DE and Western blotting, whereas 6 pairs of extracted proteins from OSCC and its adjacent non-malignant tissues were subjected to label free LC-MS. A total of 27 differently expressed proteins in iv OSCC were identified. Among these proteins; LRG, A1BG, PRO2044, ACTBM, HBB, CRNS1, HBA, F8WAH6 and SCND3 were found to be uniquely expressed in OSCC when compared with other cancers. These proteins may have the potential as specific biomarkers for OSCC. SYNE1 (Nesprin-1) was the only biomarker identified by both genomic and proteomic approach. Lastly, functional enrichment and pathway analysis were also performed on these 77 potential biomarkers using ConsensusPathDB, DAVID v6.8 and STRING v10.1 to elucidate the biological function and pathways associated with OSCC. Based on these analyses, the most significant biological function of these biomarkers in OSCC was its involvement with exosomes in the extracellular region. Whereas, the most significant pathway identified was the platelet activation, signalling and aggregation pathway. Findings from both the biological function and pathway analysis indicate that the identified biomarkers play an important role in cancer metastasis. In summary, the study had successfully identified a combination of 13 novel potential biomarkers and further improved our current understanding on the biological functions and pathways associated with OSCC. However, further studies are required to validate these biomarkers in a larger cohort and to fully understand the role of these biomarkers in OSCC.